The Role of Islamic Spirituality in Promoting Mental Health and Well-Being: A Systematic Literature Review - Retno Anggraini (Islamic Studies Journal (ISLAM), 2024)
This study aims to explore and analyze the comparative effects of Islamic spirituality on mental health and well-being by considering differences by age group and gender. Using a systematic literature review approach, this study examines various literature to identify and assess the impact of Islamic spirituality on various demographics. The results showed that Islamic spirituality had a significant effect on mental health and well-being, with marked differences by age and gender. For adolescents, Islamic spirituality contributes to increased self-identity, stress management, and reduced anxiety. Young adults experience increased social support and resilience, while older adults experience calm, life satisfaction, and reduced loneliness. From a gender perspective, men show increased self-control and emotional management, while women experience improved emotional and social well-being. These findings provide valuable insights for the development of Islamic spirituality-based interventions and mental health policies, and open opportunities for further research in this area.